A CCD BVI Photometric Study of the Young, Highly Reddened Open Cluster NGC 6318 - Piatti, Andres Eduardo (2005)
We present CCD BVI photometry for the southern open cluster NGC 6318. The sample consists of 9876 stars measured in an area of , extending down to mag. Star counts carried out 13 .6 # 13 .6 V ∼ 21.5 within and outside the cluster region allowed us to estimate the cluster angular radius as ∼8 . The comparison of the cluster color-magnitude diagrams with isochrones of the Geneva group yields , E(B V) p 1.20 0.05 E(V I) p 1.55 0.10, and for ( Myr) and . NGC V MV p 15.45 0.35 log t p 8.20 t p 160 Z p 0.020 6318 is then located at kpc from the Sun and 30 pc below the Galactic plane. Using the WEBDA open 2.1 0.5 cluster database, we examined the structure of the Galactic disk along the line of sight of NGC 6318. Among the known clusters in this direction, HM 1 and BH 222 are the farthest ones, while those located between 1 and 2 kpc of the Sun appear to be more absorbed than those expected to follow a quasi-linear extinction law.